Risk of peripheral arterial disease in patients with periodontitis: A nationwide, population-based, matched cohort study. (March 2020) - Cho, Dong-Hyuk; Song, In-Seok; Choi, Jimi; Gwon, Jun Gyo
Abstract: Background and aims: The association between coronary heart disease (CHD) caused by atherosclerosis and periodontitis has already been established. Peripheral arterial disease (PAD) is also caused by atherosclerosis, but the characteristics of the target artery and the disease are different from those of CHD. The aim of this study was to determine whether the risk of PAD was high in patients with periodontitis. Methods: For this study, we used data from the Korean National Health Insurance Service-Health Screening Cohort (NHIS-HEALS) database that were collected between January 2003 and December 2014. We compared the incidence of PAD between patients with periodontitis and a matched control group selected from among 514, 832 people enrolled in the NHIS-HEALS database to confirm the increased incidence of PAD in patients with periodontitis. Results: The incidence per 1000 person-years was 2.40 in the patients with periodontitis and 2.08 in the matched controls. The hazard ratio (HR) of PAD in the periodontitis group compared with that in the matched group was 1.15 (95% confidence interval, 1.07–1.23). In the subgroup analysis, sex, age, smoking, and hypertension statistically modified the influence of periodontitis on PAD risk. Conclusions: Control of periodontitis is important in the prevention of PAD, in addition to correcting conventional risk factors such as diabetes mellitus, hypertension, dyslipidemia, and smoking. Graphical abstract: Image 1 Highlights: Patients with periodontitis have a high incidence of peripheral arterial disease. Poor oral hygiene risk factors increase the risk of peripheral arterial disease. Control of periodontitis is important for preventing peripheral arterial disease.